2011
DOI: 10.1016/j.gie.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a risk factor for sedation-related complications during propofol-mediated sedation for advanced endoscopic procedures

Abstract: Background There is limited data on the safety of anesthesia-assisted endoscopy using propofol-mediated sedation in obese individuals undergoing advanced endoscopic procedures (AEPs). Objective To study the association between obesity [as measured by body mass index (BMI)] and the frequency of sedation-related complications (SRCs) in patients undergoing AEPs. Design Prospective cohort study. Setting Tertiary referral center. Patients 1016 consecutive patients undergoing AEPs [BMI<30: 730(72%), 30-35:15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 30 publications
(35 reference statements)
4
93
2
3
Order By: Relevance
“…Most studies suggest that the comorbidities indirectly associated with obesity, rather than obesity itself, increases the risks in same day surgeries. Clinical trials report a statistically significant higher incidence in respiratory events (oxygen desaturation, bronchospasm, stridor/laryngospasm, airway obstruction) and need for oxygen supplementation in obese patients [60,61]. However, these studies did not report an increase in unanticipated admission rates in obese patients, suggesting that the respiratory events which are a direct consequence of obesity may not be clinically significant [58].…”
Section: Who Is the High-risk Candidate For Surgery?mentioning
confidence: 97%
“…Most studies suggest that the comorbidities indirectly associated with obesity, rather than obesity itself, increases the risks in same day surgeries. Clinical trials report a statistically significant higher incidence in respiratory events (oxygen desaturation, bronchospasm, stridor/laryngospasm, airway obstruction) and need for oxygen supplementation in obese patients [60,61]. However, these studies did not report an increase in unanticipated admission rates in obese patients, suggesting that the respiratory events which are a direct consequence of obesity may not be clinically significant [58].…”
Section: Who Is the High-risk Candidate For Surgery?mentioning
confidence: 97%
“…The net effect of these physiologic changes can increase or decrease the required dose of sedatives (22). A prospective study of over 1000 obese patients found that high BMI and low anesthesiologist expertise were strong predictors of propofol sedation-related complications, highlighting the fact that the increased risk of sedation in obese patients can be managed by experienced providers (28). Dosing sedatives in obese patients by ideal body weight will result in subtherapeutic doses, whereas using total body weight (TBW) will result in overdoses (29).…”
Section: Intraprocedural Sedation Managementmentioning
confidence: 99%
“…Subjects with an elevated STOP-BANG score were also found to be at increased risk for apnea (OR: 1.63; 95% CI: 1.19, 2.25). Similarly, obesity defined as a BMI > 30 kg/m 2 was associated with an increased risk of sedation-related complications during anesthesiologist-directed propofolmediated sedation for advanced endoscopic procedures [8].…”
Section: Cardiopulmonary Risk Assessment and Consequencesmentioning
confidence: 99%
“…Important prerequisites for this type of approach include a dedicated anesthesia staff who engage in active airway management throughout the case as well as the use of monitoring including pulse oximetry, electrocardiogram, blood pressure, and either capnography or visual inspection to detect apnea. Many case series have found this approach to be quite effective [6][7][8]18]. It also appears to have a very high safety profile but comparative numbers to propofol-mediated sedation with endotracheal intubation are not available to definitively answer the safety issue.…”
Section: Patient's Positionmentioning
confidence: 99%